+0  
 
0
68
1
avatar

The second of two numbers is the first diminished my 6. Their sum is 12. Find the numbers.

Guest Dec 11, 2017

Best Answer 

 #1
avatar+5931 
+1

Let's call the first number  " f "  and the second number  " s " .   We know...

 

s  =  f - 6

                      and

s + f  =  12

 

Plug in   f - 6   for   s   into the second equation.

 

(f - 6) + f   =   12

2f - 6   =   12

2f   =   18

f   =   9               Use this value for  f  in the first equation to find  s  .

 

s   =   f - 6   =   9 - 6   =   3

hectictar  Dec 11, 2017
Sort: 

1+0 Answers

 #1
avatar+5931 
+1
Best Answer

Let's call the first number  " f "  and the second number  " s " .   We know...

 

s  =  f - 6

                      and

s + f  =  12

 

Plug in   f - 6   for   s   into the second equation.

 

(f - 6) + f   =   12

2f - 6   =   12

2f   =   18

f   =   9               Use this value for  f  in the first equation to find  s  .

 

s   =   f - 6   =   9 - 6   =   3

hectictar  Dec 11, 2017

7 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details